Expression and prognostic value of JAM-A in gliomas - Rosager, Ann Mari (J Neurooncol, 2017)
Gliomas are among the most lethal cancers, being highly resistant to both chemo- and radiotherapy. The expression of junctional adhesion molecule-A (JAM-A) was recently identified on the surface of stem cell-like brain tumor-initiating cells and suggested to function as a unique glioblastoma niche adhesion factor influencing the tumorigenic potential of brain tumor-initiating cells. We have recently identified high JAM-A expression to be associated with poor outcome in glioblastomas, and our aim was to further investigate the expression of JAM-A in gliomas focusing especially on the prognostic value in WHO grade II and III gliomas. JAM-A protein expression was evaluated by immunohistochemistry and advanced quantitative image analysis with continuous estimates of staining intensity. The JAM-A antibody stained tumor cell membranes and cytoplasm to various extent in different glioma subtypes, and the intensity was higher in glioblastomas than low-grade gliomas. We could not detect an association with overall survival in patients with grade II and III tumors. Double-immunofluorescence stainings in glioblastomas revealed co-expression of JAM-A with CD133, SOX2, nestin, and GFAP in tumor cells as well as some co-expression with the microglial/macrophage marker IBA-1. In conclusion, JAM-A expression was higher in glioblastomas compared to low-grade gliomas and co-localized with recognized stem cell markers suggesting an association of JAM-A with glioma aggressiveness. No significant association between JAM-A expression and overall survival was found in grade II and III gliomas. Further research is needed to determine the function and clinical impact of JAM-A in gliomas. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11060-017-2555-0) contains supplementary material, which is available to authorized users.